Design of actuator of orientation system of spacecraft with using automation means; Korus 2004; Vol. 3 - Taracenko A. V. (2004, 2004)
Automation parametrical row designing of spacecraft actuator based on powered by speed motor-flywheel is discussed in this paper. Automation designing systems allow essentially reduce device development time, to make better designing. During designing powered by speed, motor-flywheel was used complex CAD/CAM/CAE-system based on soft T-Flex developed by Russian company "Top-system", Moscow